AUDIT KEAMANAN SISTEM INFORMASI DENGAN COBIT 2019 PADA DOMAIN APO13 DI PT SARASWANTI INDOLAND DEVELOPMENT TBK - Bagus Setya; Feby Charlos; Lisdianto Dwi Kesumahadi (LPPM Unbaja, 2026)
This study aims to evaluate the quality of data and information security at PT Saraswanti Indoland Development Tbk through the development of an Information System (IS) based on the COBIT 2019 framework. Data and information security play a critical role in maintaining business continuity in the current digital era, particularly for companies operating in the property development industry such as PT Saraswanti Indoland Development Tbk. The selection of COBIT 2019 is based on its comprehensive approach to information system security, encompassing areas such as planning and organization, acquisition and implementation, delivery and support, as well as monitoring and evaluation. The objective of this research is to identify weaknesses in existing information system procedures, specifically focusing on data and information security, and to provide recommendations for improvement measures that can be implemented to strengthen security practices. This study employs a qualitative analysis method conducted through in-depth interviews with key stakeholders and the distribution of questionnaires. Based on the findings, recommendations for the design of an information system security framework with more stringent security standards are formulated. By implementing an information system security audit designed in accordance with COBIT 2019, PT Saraswanti Indoland Development Tbk aims to enhance the quality of data and information security, thereby supporting the company’s long-term sustainability and growth.